PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN SISWA PADA SEKOLAH MENENGAH KEJURUAN NEGERI 4 KLATEN - Poniman, Budhi; ., Kusmardi (-)
The information era is the era that content of change. As Public Organization the Government of Vocational High School 4 at Klaten must to focus for service quality than profit and birocation oriented. The purpose of this research is to prove the influence of service quality to student satisfacion of student at The Government of Vocational High School 4 at Klaten as individually and as simulate. The Hypothesis which has been formulated in this research is: there is influence which significance of among tangible, reliability, and responsiveness, assurance, and empathy, student satisfaction of student at The Government of Vocational High School 4 at Klaten as individually and also by simulate. The method used in this research is survey which using questioners for getting data. Population in this study is student at The Government of Vocational High School 4 at Klaten. Sample in this study is taken with quota random sampling. The test have done with multiple regression, t test, F test and R 2.. Regression model had done show that tangible; reliability, responsiveness, assurance, and empathy have significance influence toward student satisfaction at as individually. Result from The F show that tangible, reliability, responsiveness, assurance, and empathy, toward student satisfaction as simulate and From R test have 0,653 so that independence variable can explain dependent variable as more 65,3%. The result of test which have been conducted with the regression model , t test , test the F and also test the R have proved that fourth of the variable above can become the predictor to variable of student satisfaction Keyword: tangible, reliability, responsiveness, assurance, empath, satisfaction